USP39 at the crossroads of cancer immunity: regulating immune evasion and immunotherapy response through RNA splicing and ubiquitin signaling - Zhou, Feilong; Li, Xinhao; Sun, Yanmei; Wang, Yizhu; Niu, Kaiyi; Gao, Xin; Zhang, Jiaqi; Chen, Tianyi; Li, Yunxin; Zhao, Weijie; Mao, Binyue; Xu, Qiyang; et al. (Frontiers in Immunology, 2025)
Deubiquitinating enzymes (DUBs) are responsible for the removal of ubiquitin from substrates, thereby antagonizing ubiquitination and regulating a multitude of biological pathways including cell cycle progression, signal transduction, and transcriptional regulation. Ubiquitin Specific Protease-39 (USP39), a pivotal member of the ubiquitin-specific protease family, is intricately linked to innumerable pathophysiological processes. In this review, we first provide an overview of the specific structural domains and biological functions of USP39, with a particular focus on its role in DNA damage repair and RNA splicing processes. Then, we delineate the function of USP39 in maintaining epithelial morphology, resistance to viral infection, vascular remodeling, and pathological states. Moreover, we particularly focus on the aberrant expression of USP39 in various cancers and its effect on cancer markers, as well as on the regulatory role of USP39 in tumor progression. In conclusion, a comprehensive analysis of the structural domains and functional properties of USP39, a detailed investigation into its interaction mechanisms with diverse substrates, and the accelerated development of related inhibitors will provide a novel theoretical foundation for the treatment of numerous diseases, including tumors. Importantly, targeting USP39 may overcome resistance to checkpoint inhibitors, offering a promising approach to enhance cancer immunotherapy efficacy.